Design, manufacture and performance analysis of an automatic antenna tracker for an unmanned aerial vehicle (UAV) - Gesang Nugroho; Dicky Dectaviansyah (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2018)
In conducting a disaster monitoring mission, an unmanned aerial vehicle (UAV) has to travel a long distance to cover the region that is hited by a disaster. In the monitoring mission, Air Data and Attitude Heading Reference System (ADAHRS) data are very important to always be displayed on the ground control station (GCS). Unfortunately, the area of monitoring mission is very wide, whereas the usage of an omnidirectional antenna in the disaster monitoring mission is limited to the UAV maximum range. Therefore, a high gain directional antenna is needed. However, the directional antenna has a disadvantage of always being directed to the target. To solve this problem, antenna tracker is made to track the UAV continuously so that the directional antenna can always be directed to the flying UAV. An antenna tracker using a 32-bit microcontroller and GPS with two degrees-of-freedom was developed. It is able to move 360 degrees on azimuth axis (yaw) and 90 degrees on elevation axis (pitch). Meanwhile, the directional antenna is three elements yagi type with a radiation capability of 6 dBi. By using the antenna tracker, larger UAV range was obtained and the connection between the UAV and the GCS could always be maintained with a minimum fluctuation of RSSI signal, compared to those without using antenna tracker.